Hubungan Jenjang Karir Perawat Dengan Kepuasan Kerja Perawat Pelaksana Di Rawat Inap Rsud Haji Abdoel Madjid Batoe Batanghari - Faizatul Jannah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Nursing career pathways in Indonesia have been established by the Indonesian National Nurses Association (PPNI) in collaboration with the Miinistry of Health through the formulation of nursing career path guidelines. Job satisfaction among nurses is closely tied to their career progression. Situated in Batanghari, Haji Abdoel Madjid Batoe Hospital is one of the healthcare facilities where nurses reported lower levels of satisfaction, attributed to suboptimal functioning of the career advancement system. The objective of the study is to incvestigate the correlation between nuvrse cvareer development and job satisfaction among executive nurses at Haji Abdoel Madjid Batoe Batanghari Hospital. Conducted as a quantitativve research endeavor with a cross-sectional design, this study transpired between July 3, 2023, and July 17, 2023, at RSUD Haji Abdoel Madjid Batoe Batanghari. The targeted population comprised 128 inpatient nurses, with a samvple size of 57 respvvondents selected using purposive sampling methodology. The statistical analysis employed was the chi-square test. Findings from the research revealed that a significant proportion of respondents exhibited a favorable career path trajectory (66.7%), although the majority expressed dissatisfaction with their job (52.6%). Notably, a notable association between nurse career stage and job contentment was identified (p = 0.001).